The Humidity in a Drager Primus Anesthesia Workstation Using Low or High Fresh Gas Flow and With or Without a Heat and Moisture Exchanger in Pediatric Patients - Bicalho, Gustavo P. [UNESP]; Braz, Leandro Gobbo [UNESP]; Jesus, Larissa S. B. de [UNESP]; Pedigone, Cesar M. C. [UNESP]; Carvalho, Lidia R. de [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Braz, José Reinaldo Cerqueira [UNESP] (Lippincott Williams & Wilkins, 2014)
BACKGROUND: An inhaled gas absolute humidity of 20 mg H2O.L-1 is the value most considered as the threshold necessary for preventing the deleterious effects of dry gas on the epithelium of the airways during anesthesia. Because children have small minute ventilation, we hypothesized that the humidification of a circle breathing system is lower in children compared with adults. The Primus anesthesia workstation (Drager Medical, Lubeck, Germany) has a built-in hotplate to heat the patient's exhaled gases. A heat and moisture exchanger (HME) is a device that can be used to further humidify and heat the inhaled gases during anesthesia. To evaluate the humidifying properties of this circle breathing system during pediatric anesthesia, we compared the temperature and humidity of inhaled gases under low or high fresh gas flow (FGF) conditions and with or without an HME.METHODS: Forty children were randomly allocated into 4 groups according to the ventilation of their lungs by a circle breathing system in a Drager Primus anesthesia workstation with low (1 L.min(-1)) or high (3 L.min(-1)) FGF without an HME (1L and 3L groups) or with an HME (Pall BB25FS, Pall Biomedical, East Hills, NY; HME1L and HME3L groups). The temperature and absolute humidity of inhaled gases were measured at 10, 20, 40, 60, and 80 minutes after connecting the patient to the breathing circuit.RESULTS: The mean inhaled gas temperature was higher in HME groups (HME1L: 30.3 degrees C +/- 1.1 degrees C; HME3L: 29.3 degrees C +/- 1.2 degrees C) compared with no-HME groups (1L: 27.0 degrees C +/- 1.2 degrees C; 3L: 27.1 degrees C +/- 1.5 degrees C; P < 0.0001). The mean inhaled gas absolute humidity was higher in HME than no-HME groups and higher in low-flow than high-flow groups ([HME1L: 25 +/- 1 mg H2O.L-1] > [HME3L: 23 +/- 2 mg H2O.L-1] > [1L: 17 +/- 1 mg H2O.L-1] > [3L: 14 +/- 1 mg H2O.L-1]; P < 0.0001).CONCLUSIONS: In a pediatric circle breathing system, the use of neither high nor low FGF provides the minimum humidity level of the inhaled gases thought to reduce the risk of dehydration of airways. Insertion of an HME increases the humidity and temperature of the inhaled gases, bringing them closer to physiological values. The use of a low FGF enhances the HME efficiency and consequently increases the inhaled gas humidity values. Therefore, the association of an HME with low FGF in the breathing circuit is the most efficient way to conserve the heat and the moisture of the inhaled gas during pediatric anesthesia.